Truth, Justice, and Sexual Violence: A Comparative Analysis of Op-Eds Surrounding the Hill-Thomas and Ford-Kavanaugh Hearings. (10th December 2021) - Boling, Kelli S.; Moscowitz, Leigh
ABSTRACT: Using discourse analysis to examine newspaper Op-Eds during the Hill-Thomas and Ford-Kavanaugh hearings, this study explores how media can function as an arbiter of public opinion during controversial events. This analysis highlights the importance of Op-Eds in defining whose voices matter in shaping national mediated discourses, examining the role media play in critical public debates surrounding issues of gender, race, power, and sexual violence. Against a backdrop of increasing numbers of women in the Senate chambers, the growing numbers of women and people of color across American newsrooms, and the impact of the #MeToo movement in the national conversation about sexual violence, this study examines changes in opinion authorship and media discourses surrounding these two hearings set 27 years apart. Findings show a shift in Op-Ed contributors, from mostly men in 1991 to predominantly women in 2018. Support for women and sexual assault accusers was largely absent in Op-Eds from 1991, replaced by vague debates about fairness and justice; while in 2018, Op-Ed authors offered tangible support for accusers. This study considers both the promise and limitations of these shifting media discourses to address structural and institutional power relations.